Dental Caries: Empowering School Teachers as Today's Smile Heroes for Children - Prabowo, Kukuh Eko (BKM Public Health and Community Medicine, 2024)
Purpose: Dental caries is a prevalent chronic disease among children, affecting up to 93% in Indonesia. This study aims to optimize the role of teachers as today's smile heroes through empowerment initiatives. Methods: Many parents still believe that dental issues in children are insignificant because their primary teeth will eventually be replaced by permanent ones. However, evidence shows that the first permanent molars typically emerge around 6-7 years and are most susceptible to caries. This susceptibility is due to children frequently consuming cariogenic foods such as chocolate, candy, cakes, and sugary drinks without maintaining proper oral hygiene. Such habits increase the risk of dental caries, which can lead to severe health issues like gingivitis and periodontitis, affecting food mastication. The exposure to advertisements for cariogenic foods on social media and television also influences children's purchasing behavior. The current availability of school-based dental caries prevention programs (UKGS) is inadequate. Empowering school teachers as smile heroes can maximize the potential resources within schools. Results: Trained school teachers can help detect dental health issues early, allowing for timely interventions before problems escalate into more severe conditions. By empowering teachers as smile heroes in dental caries prevention, schools can create an environment that supports optimal dental and oral health for children, promoting healthy smiles. This initiative is crucial to support the “Indonesia Free from Caries 2030” program by the Ministry of Health of the Republic of Indonesia, aiming to reduce the prevalence of dental caries among children. Conclusion: Empowering school teachers is essential for improving children's dental health. Trained teachers can effectively detect and address dental problems early, fostering a supportive environment for optimal oral hygiene and contributing to the national goal of reducing childhood dental caries.